CONTRIBUTION OF TOLL-LIKE RECEPTORS AS A THERAPEUTIC TARGET IN ADJUVANT INDUCED ARTHRITIC RAT MODEL - Kahkashan Perveen; Shabana Usman Simjee; Farina Hanif; Saima Mahmood Malihi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Rheumatoid arthritis (RA) is an inflammatory joint disease characterized by a variety of abnormal cellular processes. Toll-like receptors (TLRs) have been linked to immunological abnormalities in RA patients.Objectives: The purpose of this study was to look at the role of TLR2 and TLR4 in progression of arthritis and their modulation by N-(2-hydroxyphenyl) acetamide.Material and Methods: Arthritis was induced in rats by Heat-killed Mycobacterium tuberculosis (MT37Ra). Progression and impact of disease was observed macroscopically and at molecular level. Reactive oxygen species (ROS) and antioxidants production was estimated in serum to assess the immune response.Results: We observed over expression of TLRs on bone marrow cells parallel to the severity of arthritis progression in arthritic control group. Over-expression of TLRs triggered ROS expression followed by a decrease in antioxidants resulting in destruction of bones and cartilage in arthritic control group. Treatment with N-(2-hydroxyphenyl) acetamide (NA-2) reduced  severity of arthritis by reducing the expression of toll like receptors  TLR2 (*P < 0.043) and TLR4 (**P < 0.001) on BMCs in arthritic rats . Production of  Reactive oxygen species  , a marked increase in the GSH and SOD .ConclusionsOur findings suggest that TLRs may play a role in the etiology of arthritis by causing direct activation of BMCs. Our data further suggest that NA-2 inhibits TLR-mediated joint inflammation and other arthritis-related symptoms, implying that it could be used to treat arthritis.